Mewujudkan Hak-Hak Disabilitas Dalam Lingkungan Universitas Pendidikan Indonesia (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Human rights, especially the right to education for children with special needs, are guaranteed by various national and international regulations. The aim is to reveal the awareness of students at Indonesia University Of Education regarding the importance of the rights and obligations to go to school and obtain education for all people, including people with disabilities. Based on observations, there is a lack of concern for friends with disabilities who have not fully received their rights. This research uses a descriptive qualitative approach to collect and analyze data related to the implementation of disability rights in the campus environment. The methods used included a literature study, preparation of question instruments, interviews, and observations of a sample of students from various study programs. The results highlight the importance of inclusive education and accessibility for people with disabilities, as well as the role of educational institutions in shaping the identity and values accepted by individuals and society.